Actualization of Semantic Roles in Protest Communication (on Material of German Online Petitions) - L. N. Rebrina; L. M. Generalova (Научный диалог)
This paper examines the linguistic representation of situations of online protest petitions. The specificity of the implementation of semantic roles in the semantic predicate of action expressed by potentially performative verbs, which names the corresponding intention, is considered. Attention is paid to the characteristic of online petitions as a genre of protest communication, performativity as a property of language expressions, determination of the categorical status of the semantic predicate and semantic case, participation of the significative interpretation in alternative perception and linguistic representation of situations. The relevance of the work is determined by the need to study the discursive specifics, pragmatic parameters of new online genres of protest communication, the possibility and prospects of studying universal conceptual categories on the example of the case system and their role in the formation of language categories, the importance of understanding the degree of influence of ontological factors on the formation of language consciousness. The results of the study of the set of semantic-syntactic relations and paradigm of means of expression of semantic roles in the framework of the three communicative-semantic groups of statements, implementing the basic text-forming intentions such as consent / support, disagreement / disapproval, requirement / request, are presented. Features of the implementation of performativity in the named genre of electronic democracy, determined by discourse, are identified. The means of grammaticalization of pragmatic parameters of performativity in the analyzed material are described.